Infection of Animals with the Influenza Virus after a Preliminary Administration of Preparation "Cryocell-Haemocord". Report III. Study of Morphofunctional State of Mice Lungs - Goltsev, A. N.; Volina, V. V.; Onasenko, E. S.; Goltsev, K. A.; Kozhina, O. Yu.; Ponomareva, V. L. (Problems of Cryobiology and Cryomedicine, 2010)
There has been studied the effect of preliminary adminstration of "Cryocell-Haemocord" preparation on morphofunctional state of lungs, as well as there was investigated the content of influenza virus A/Victoria in murine organs infected with it in a lethal dose. The findings testify to an anti-viral effect of "Cryocell-Hemocord" preparation, manifesting in the absence of dystrophic and necrotic impairments in lungs of the animals infected after its introduction.